TRANSLATION STRATEGIES FOR AFGHAN CULTURAL TERMS IN KHALED HOSSEINI’S FICTION - Khayrieva Madina Ilhomovna (International Journal of Literature and Language Studies, 2026)
This article examines the translation strategies employed in rendering Afghan cultural terms found in Khaled Hosseini’s major novels. The article argues that successful translation of Hosseini's translingual units requires a dynamic strategy that shifts between retention, contextual amplification, and selective domestication according to the semantic weight and narrative function of each term.